The LEGAL STATUS AND ACQUISITION OF MEDIATOR QUALIFICATIONS. A LEGAL COMPARATIVE ANALYSIS OF THE REGULATIONS IN SPAIN AND POLAND - Dąbrowski, Marek; Broński, Włodzimierz; Concepción Rayón Ballestero, María (Review of European and Comparative Law, 2023)
The article aims to analyze the legal status and modes of acquiring qualifications by mediators in Poland and Spain. The study uses the legal dogmatic and the legal comparative methods. The research problem lies in the applicable solutions in Polish and Spanish legislation implementing the objective set out by the content of Article 4 of Directive 2008/52/EC, which obliges EU Member States to ensure adequate quality of mediation and enhance the professional status of the mediator. An analysis of the legislation, judicature, and the literaturę on the subject has shown that the normative regulations which are in force in Spain and Poland are convergent in terms of the objectives set out in Article 4 of Directive 2008/52/EC since they oblige mediators to be adequately qualified to conduct mediation. Notwithstanding the above, significant differences in the legal systems under analysis becomes apparent as concerns an array of legal instruments they apply to implement the Directive. The Polish and the Spanish methodologies display disparate procedures for regulating the acquisition of qualifications by mediators. They suffer from a number of shortcomings, resulting from an insufficient level of standardization, including the intra legem gaps in the normative regulations in Poland. The outcomes of the analysis enable the conclusion that the regulations concerning the legal status and qualifications of mediators that are in force in Poland and Spain can complement one another while preserving and respecting the distinctiveness of both legal systems. This complementarity can facilitate the development of an adequate model to enhance the professional status of mediators and improve the regulations so as to achieve the objective set in Article 4 of Directive 2008/52/EC.